The effect of ethanol-gasoline blends on SI engine energy balance and heat transfer characteristics - Alrayyes, Taleb (2011)
Ethanol is one of a group of hydrocarbon fuels produced from bio-mass which is attracting interest as an alternative fuel for spark ignition engines. Major producers of ethanol include Brazil, from sugar cane, and the USA, from com. Reasons for the growing interest in ethanol include economic development, security of fuel supply and the reduction of net emissions of carbon dioxide relative to levels associated with the use of fossil fuels. Unlike gasoline, which is a mixture of hydrocarbon compounds suited to meet a range of start and operating requirements, ethanol is a single component fuel with characteristics which make engine cold starting difficult, for example. Hence, ethanol is generally used in a blend with gasoline, accounting for <5% in EU pump-grade gasoline to 85% by volume for so called flex-fuel vehicles.